Association between the nutritional and biochemical profile of oncological patients in a reference hospital in Belém Pará (Research, Society and Development, 2022)
Objective: To analyze the nutritional profile of cancer patients and relate it to their biochemical data. Methodology: Descriptive and analytical study, with a transversal characteristic, carried out with cancer patients. The variables used in the study included: clinical diagnosis, sex, age, anthropometric measurements and biochemical tests. From this, the collected data were analyzed using the BioEstat 5.0 software. The Mann-Whitney tests and the chi-square test (x²) were used, with a significance level of 5% for the entire study. Results: 64 patients, 58% female and 42% male. 38 are adults with a mean age of 49.13 ±7.38 and 26 elderly with a mean age of 71.07 ±5.93. Regarding the nutritional status of patients, according to BMI, 27% of patients were thin, according to arm circumference (AC) 28% were depleted. Regarding the biochemical exam data, 78% had a hemoglobin level below the limit, characterizing anemia, and only 22% had an adequate level of hemoglobin. There was a statistically significant association between nutritional status according to BMI and age and biochemical tests, as well as between nutritional status according to BC and age and biochemical tests. Conclusion: There was a relevant number and significant statistical association of malnutrition and anemia, demonstrating the need for attention to cancer patients, in order to reduce the risks of morbidity and mortality of these individuals.